2016
DOI: 10.18869/nrip.jamsat.2.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and Novel Forms of Silver in Medicine and Biomedicine

Abstract: Silver cations have been known as potent antimicrobial agents since ancient time and were used in burns, wounds and ulcers treatment(1). Silver was known to the Chaldeans as early as 4,000 B.C.E, and it was the third metal known to be used by the ancients, after gold and copper(2). Silver colloids have been used for numerous medical conditions, mostly empirically before realizing that microbes were the agents causing infection. The ancient Phoenicians, Greeks, Romans and Egyptians had used silver compounds as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 75 publications
0
28
0
3
Order By: Relevance
“…Silver nanoparticle (AgNPs) are one of the most studied and applied nanoparticles in medicine and biomedicine. These particles are well known as a potent antimicrobial against almost all bacterial strains (Ebrahiminezhad et al, 2016a;2016b;2016d). AgNPs are also effective against antibiotic resistant microorganisms and increase the efficiency of antibiotics (Devi and Joshi, 2012;Fayaz et al, 2011;Ruden et al, 2009;Shahverdi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticle (AgNPs) are one of the most studied and applied nanoparticles in medicine and biomedicine. These particles are well known as a potent antimicrobial against almost all bacterial strains (Ebrahiminezhad et al, 2016a;2016b;2016d). AgNPs are also effective against antibiotic resistant microorganisms and increase the efficiency of antibiotics (Devi and Joshi, 2012;Fayaz et al, 2011;Ruden et al, 2009;Shahverdi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…81,82 Oxidative stress mediate mechanisms that damage carbohydrates, lipids, proteins, and DNA, which leads to disturbing vital cellular functions and cell death. [83][84][85][86][87] Scientists reported that various metal nanoparticles have shown different cell viability results with regard to their ability to produce oxidative stress and induce cell injury. [88][89][90] Furthermore, SPION could result in significant changes in the cell medium, such as protein denaturation, which can cause toxicity.…”
Section: Vsmmentioning
confidence: 99%
“…These nanostructures are now used in Magnetic Resonance Imaging (MRI), magnetic transfection, hyperthermia, DNA and cell labelling, tissue engineering, and targeted drug delivery [24][25][26][27][28][29][30][31][32][33][34]. Biosynthesized nanostructures are more interesting for these biomedical applications due to high biocompatibility and high physicochemical stability [35][36][37][38][39][40][41][42].…”
Section: Iron Reducing Bacteria and Iron Nanoparticlesmentioning
confidence: 99%